Adoption of Family Financial Management Strategy Towards Financial Resilience - Christina Heti Tri Rahmawati; Caecilia Wahyu Estining Rahayu; Lukas Purwoto; Josephine Wuri (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2025)
Purpose Family financial management as a process of managing income, expenses, savings, and investments related to financial resources so as to improve family welfare. The higher the income, the better the quality of family life. However, in reality, the amount of money owned does not necessarily guarantee financial resilience. Families with healthy financial conditions have the potential to achieve more. This community service activity raises the problems faced by Principal Teachers from kindergarten to junior high school levels at a private foundation in the Special Region of Yogyakarta Province in facing increasingly complex economic challenges, where not only is there a lack of financial management knowledge but also an inability to plan savings, debt management, lack of understanding of investment, and limited access to information related to finance. Therefore, the adoption of a family financial management strategy is important so that it can improve family financial resilience. This counseling activity aims to provide an understanding of the importance of adopting a family financial management strategy as the main pillar so that sustainable financial resilience can be achieved. Methods - This outreach activity was carried out with a holistic approach that combines educational, participatory, and collaborative aspects regarding the adoption of family financial management strategies for Principal Teachers from Kindergarten to Junior High School levels at a private foundation in the Special Region of Yogyakarta Province so that they can achieve sustainable financial resilience. The method is designed to ensure in-depth understanding and real application in everyday life. Result and discussions - The results of the counseling are expected to improve the understanding of adopting family financial management strategies for Principal Teachers from Kindergarten to Junior High School levels at a private foundation in the Special Region of Yogyakarta Province. Concrete achievements include the ability to have emergency funds of 3 to 6 times monthly income, loan installments of no more than 35% of monthly income, and the ability to save at least 10% of income every month. Conclusion – The implication of the results of this community service activity is that it is hoped that Principal Teachers from Kindergarten to Junior High School levels at a private foundation in the Special Region of Yogyakarta Province can adopt family financial management strategies so that they can achieve sustainable financial resilience that has an impact on family welfare.